A qualitative study on violent extremists and news media : how Malaysian online news framed violent extremist groups involved in the Syrian civil war - Nurul Miza Mohd Rashid,; Fahad Riaz, (Penerbit Universiti Kebangsaan Malaysia, 2022)
e news has been a place for violent extremist groups to gain recognition internationally. The Syrian Civil war which had involved notorious and internationally recognised violent extremist groups is an example of this phenomenon. However, a limited number of studies had uncovered the thematic variation on how Malaysian online news frames violent extremist groups involved in the Syrian Civil War. Therefore, the present study explored whether the Malaysian news coverage of the violent conflicts that involved violent extremist groups active during the Syrian civil war may shed light on how mainstream news covers violent extremist groups. The present study employed a qualitative search and analysis of two popular online newspapers in Malaysia to identify the types of news frames on the news published during the peak of the Syrian civil war and when a notorious violent extremist group, Daesh (alternatively known as Islamic State (IS) or Islamic State of Iraq and Syria (ISIS)), had shaken and threatened the world. A total of 272 news articles published between 2010 to 2020 were collected and analyzed. Analysis of the news frames revealed twelve different news frames. The frame with the highest occurrence was labelled as “Western destructive interventions”. The frame detailed out Western nations’ involvement in the war which caused damage to livelihood and civilizations in Syria and justified the violent extremist groups’ activities. The present study concludes that the Malaysian news media framing on violent extremist groups and other parties involved in the Syrian Civil War could have two varied forms, positive (heroic or humanized) or negative (destructive or demonized). The main contribution of this study is that it provides an insight into how Malaysian news media cover a conflict involving Muslim extremist groups. Additionally, the study adds to previous research on how violent extremist groups is framed in digital news.